Trends in Cancer and Pulmonary Embolism-related mortality in the adult U.S. population: A CDC WONDER database analysis from 1999 to 2020 - Altobaishat, Obieda; Amer, Basma Ehab; Gadelmawla, Ahmed Farid; Nadeem, Amna; Khlidj, Yehya; Almasri, Hashim; Turkmani, Mustafa; Abouzid, Mohamed (Journal of Medical Science, 2026)
Introduction. Cancer and pulmonary embolism (PE) remain significant global health challenges, with approximately 20 million new cancer cases diagnosed worldwide, resulting in 9.7 million deaths. We aimed to assess trends in PE-associated mortality among U.S. cancer patients (1999–2020).Material and methods. CDC WONDER death certificate data identified 179,044 PE-associated deaths in cancer patients (age ≥25). Age-adjusted mortality rates (AAMRs) per 100,000 were obtained, stratified by year, sex, race/ethnicity, region, and cancer type, with 95% confidence intervals. Joinpoint regression identified trends. Results. A total of 179,044 PE-associated deaths in U.S. adults with cancer were recorded from 1999 to 2020, with AAMRs rising during this period. Overall, men had higher AAMRs than women (4.2, 95% CI: 4.0–4.3 vs 3.4, 95% CI: 3.3–3.5). AAMRs were highest among NH Black/African Americans (5.7, 95% CI: 5.7–5.8); the largest absolute number of deaths occurred in Whites, and the fewest in American Indians/Alaska Natives. Most deaths (64%) occurred in medical facilities. Among cancer types, lung cancer showed the highest mortality (AAMR 1.0, 95% CI: 0.97–1.05), whereas prostate cancer had the lowest (AAMR 0.20, 95% CI: 0.20–0.21).Conclusions. PE-associated mortality in cancer patients rose from 1999 to 2020, disproportionately affecting men, NH Black/African Americans, Midwest residents, and lung cancer patients.
Keywords: neoplasm; malignancy; cancer; CDC; pulmonary embolism